Financial Report of the Director and Report of the External Auditor for 2012 - Pan American Health Organization (PAHO, 2014)
The Organization continued to provide technical cooperation in support of the public health challenges impacting the Region of the Americas in 2012. Natural disasters continue to plague our Region, including floods in Ecuador, Colombia and Peru, major earthquakes in Guatemala, Mexico and Costa Rica, as well as hurricanes Sandy and Isaac. Other challenges include the strengthening of the national immunization program in Haiti to mitigate health vulnerabilities caused by the 2010 earthquake and the cholera outbreak, the arrival of cholera in Cuba, and the avian flu outbreak in Mexico. PAHO provided technical cooperation in disaster preparedness to effectively respond to these emergencies with the financial support of its Member States and partners, exemplifying the cooperative efforts to strengthen the countries’ response capacity. In addition, PAHO inaugurated the new Emergency Operations Center in June 2012, which has enhanced the Organization’s ability to respond to challenges in public health crises and disasters. The Organization’s consolidated total revenue in 2012 reached $978.6 million, which is the highest level of revenue in PAHO’s history. The increase in revenue is primarily due to the increase in procurement services on behalf of Member States and the recognition of revenue from the transfer of the Expanded Textbook and Instructional Materials Program (PALTEX) to PAHO. Revenue to the Regular Budget totaled $99.8 million. Revenue from Voluntary Contributions for public health programs totaled $216.4 million. The Organization’s procurement activities on behalf of Member States increased from $455.9 million in 2011 to $562.4 million in 2012. The level of resources for the Organization’s three Procurement Funds represents 57% of the Organization’s total revenue. Revenue for activities funded by the World Health Organization totaled $61.6 million.